DETERMINATED SIGNALS MATHEMATICAL MODELS ON THE BASIS OF PRIMITIVE FUNCTION SYSTEMS - V. N. Isakov (Российский технологический журнал)
The article deals with universal systems on the basis of primitive functions for approximating pulse signals of different types and duration and providing simple mathematical formulation as well. Power, polynomial-cosinusoidal, exponential-multinomial, linear fractional, B-spline signal systems and restricted spectrum systems have been presented. The expressions for spectral and correlation characteristics of the signal systems mentioned have been obtained. Based on the analyzed signals models a multifunctional plug-in software module “Signals Library” has been developed. The module interface is designed for module private use (for example, as a computer reference guide) or for the external program application, for example, as a window to provide a signal type and signal parameters setting selection for users. The examples of the results obtained using the programs above mentioned as well as Signals Library module graphical presentation have been represented in the article .A matter of choice of this or that functions system can be determined by specifics of the task to be solved.